PENGEMBANGAN POTENSI WISATA BERBASIS COMMUNITY BASED TOURISM (CBT) UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA BETTENG KECAMATAN PAMBOANG - Haeruddin Hafid; Sufyan Amirullah; Sri Amalia Edy (Jurnal Abdi Insani, 2023)
Betteng Village is one of the villages that has tourism potential because of its geographical location in a mountainous area. The tourism potential it has is called "Pattumea". Pattumea is a tourist spot that has excellent potential because the scenery there is very beautiful. However, it turns out there are still very few visitors. Based on the results of observations made by the service team, it turns out that the human resource capabilities of Betteng village are still very lacking. Therefore, the service team carried out this service activity to help resolve the human resource problems of Betteng village so that its tourism potential can be even better. The solution provided is to conduct training on developing the concept of community based tourism (CBT) in managing tourism potential. Apart from that, it also provides training on the use of social media so that the marketing of tourism owned by Mitra village can be broader. The result of this service is increased knowledge of the participants regarding the concept of community based tourism in managing tourism potential involving the surrounding community. Community involvement such as being able to leave their merchandise at these tourist attractions. Apart from that, training on the use of social media is very helpful for partner villages in marketing the tourism potential they have, in this case Pattumea tourism. With this training on the use of social media, the participants learned that it is very important to do marketing using social media rather than conventional methods. Marketing using social media can expand marketing reach to other areas. Applying the CBT concept in management and utilizing social media in tourism marketing, it is hoped that Pattumea tourism can be better.